Spectroscopic scale protection factor (SSPF) of solar ultraviolet radiation molecular screens. II. Substituent effect on salicylideneaniline. Issue 3 (2000) - Morales Morales, Raúl G. E. Raúl G. E.; Hidrobo Hidrobo, Alexis Alexis; Jara Jara, Gregorio P. Gregorio P.
Abstract : Salicylideneanilines present a broad absorption band and a high molar absorption coefficient in the UV-A and UV-B regions. In addition, they are photostable compounds to the solar radiation exposition. Therefore, we have recently established their potential use as a solar ultraviolet radiation molecular screens. In the present work we have determined the dependence of the Spectroscopic Scale Protection Factor (SSPF) values with the substituent effect on the aniline ring of the salicylidene, when the substituent is an electron-acceptor group (–CN, –COCH3, –NO2 ) and we have compared this effect with and without an electron-donor group (–OCH3 ) at para position in the salicylidene ring. In order to determine and compare these SSPF values versus the usual Sun Protection Factor (SPF) values, a relative scale of biological nature, we have determined the electronic absorption spectra of these substituted salicylideneaniline compounds, and we have compared these spectroscopic data with homosalate, as an SPF standard compound. Our results are conclusive respect to determine the salicylideneanilines as a new family of molecular species highly efficient in the molecular screen role.